Influence of porosity on lipid preservation in the wall of archaeological pottery. (10th June 2019) - Drieu, L.; Horgnies, M.; Binder, D.; Pétrequin, P.; Pétrequin, A.‐M.; Peche‐Quilichini, K.; Lachenal, T.; Regert, M.
Abstract : Porosity of archaeological pottery is a key parameter used to assess its ability to trap lipids during the use of the pot and to preserve them over time. Mercury intrusion porosimetry and gas chromatography were used to study the distribution of porosity and the preservation of lipids in different chrono‐cultural contexts. The data obtained show that the porosity pattern, related to the raw materials and the savoir‐faire of the potters, influences the amount of lipids accumulated in the pottery. A significant overall porosity together with a high level of small pores is generally favourable for the preservation of lipids, but variations related to the environmental context are observed.